The impact of patient delirium in the intensive care unit: patterns of anxiety symptoms in family caregivers - Therese G. Poulin; Karla D. Krewulak; Brianna K. Rosgen; Henry T. Stelfox; Kirsten M. Fiest; Stephana J. Moss (BMC, 2021)
Abstract Background The purpose of this study was to examine the association of patient delirium in the intensive care unit (ICU) with patterns of anxiety symptoms in family caregivers when delirium was determined by clinical assessment and family-administered delirium detection. Methods In this cross-sectional study, consecutive adult patients anticipated to remain in the ICU for longer than 24 h were eligible for participation given at least one present family caregiver (e.g., spouse, friend) provided informed consent (to be enrolled as a dyad) and were eligible for delirium detection (i.e., Richmond Agitation-Sedation Scale score ≥ − 3). Generalized Anxiety Disorder-7 (GAD-7) was used to assess self-reported symptoms of anxiety. Clinical assessment (Confusion Assessment Method for ICU, CAM-ICU) and family-administered delirium detection (Sour Seven) were completed once daily for up to five days. Results We included 147 family caregivers; the mean age was 54.3 years (standard deviation [SD] 14.3 years) and 74% (n = 129) were female. Fifty (34% [95% confidence interval [CI] 26.4-42.2]) caregivers experienced clinically significant symptoms of anxiety (median GAD-7 score 16.0 [interquartile range 6]). The most prevalent symptoms of anxiety were "Feeling nervous, anxious or on edge" (96.0% [95%CI 85.2-99.0]); "Not being able to stop or control worrying" (88.0% [95%CI 75.6-94.5]; "Worrying too much about different things" and "Feeling afraid as if something awful might happen" (84.0% [95%CI 71.0-91.8], for both). Family caregivers of critically ill adults with delirium were significantly more likely to report "Worrying too much about different things" more than half of the time (CAM-ICU, Odds Ratio [OR] 2.27 [95%CI 1.04-4.91]; Sour Seven, OR 2.28 [95%CI 1.00-5.23]). Conclusions Family caregivers of critically ill adults with delirium frequently experience clinically significant anxiety and are significantly more likely to report frequently worrying too much about different things. Future work is needed to develop mental health interventions for the diversity of anxiety symptoms experienced by family members of critically ill patients. Trial registration This study is registered on ClinicalTrials.gov ( https://clinicaltrials.gov/ct2/show/NCT03379129 ).